USE OF ARTIFICIAL INTELLIGENCE IN THE IMPLEMENTATION OF PUBLIC HIGHER EDUCATIONAL ACADEMIC PROGRAMS IN KENYA: CHALLENGES AND OPPORTUNITIES - PAUL OKEYO OGEMBO; Ongoing (CV. ADIBA AISHA AMIRA, 2025)
Artificial Intelligence (AI) is a current technological approach towards implementation of programs including education in an efficient practice. However, in Kenyan higher educational institutions it appears scanty. The purpose of this study therefore is to Assess the use of AI in the implementation of public universities’ academic programs in Kenya. Specifically, the study seeks to determine whether there are AI policy frameworks for the universities; to establish the extent of universities’ investment in AI in regard to running their programs; to establish universities’ extent of integration of AI in running their academic programs and to determine the way forward on integration of AI on university programs in Kenya.The study used survey design to collect primary data of which three Public universities were sampled, out of which 3 deputy vice chancellor academics,15 chairs of departments 5 from each of the selected universities,3 university directors of ICT and 45 undergraduate students drawn from the various faculties of the three universities selected for the study. The study will be underpinned by Technology Acceptance Model by Davis (1989). The findings of the study showed that in all the three universities surveyed there existed AI policy frameworks. However, there were minimal levels of invested and integration of AI into the mainstream university programs. The findings of the study have implications for all stakeholder engagement and sensitization in regard to the importance of investing into and integrating AI into the university programs as a way being in tandem with the current digitized, efficient, cost-effective, technologically innovative model towards globalized trends.